The role of long non-coding RNA in abdominal aortic aneurysm - Xu, Yi; Yang, Shuofei; Xue, Guanhua (Frontiers in Genetics, 2023)
The abdominal aortic aneurysm (AAA) is characterized by segmental expansion of the abdominal aorta and a high mortality rate. The characteristics of AAA suggest that apoptosis of smooth muscle cells, the production of reactive oxygen species, and inflammation are potential pathways for the formation and development of AAA. Long non-coding RNA (lncRNA) is becoming a new and essential regulator of gene expression. Researchers and physicians are focusing on these lncRNAs to use them as clinical biomarkers and new treatment targets for AAAs. LncRNA studies are beginning to emerge, suggesting that they may play a significant but yet unidentified role in vascular physiology and disease. This review examines the role of lncRNA and their target genes in AAA to increase our understanding of the disease’s onset and progression, which is crucial for developing potential AAA therapies.